2018
DOI: 10.3390/ijms19092707
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Sources and Regional Variations in the Expression of the Neuroinflammatory Marker Translocator Protein (TSPO) in the Normal Brain

Abstract: The inducible expression of the mitochondrial translocator protein 18 kDa (TSPO) by activated microglia is a prominent, regular feature of acute and chronic-progressive brain pathology. This expression is also the rationale for the continual development of new TSPO binding molecules for the diagnosis of “neuroinflammation” by molecular imaging. However, there is in the normal brain an ill-defined, low-level constitutive expression of TSPO. Taking advantage of healthy TSPO knockout mouse brain tissue to validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
88
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 59 publications
(99 reference statements)
13
88
0
1
Order By: Relevance
“…A recent study by Betlazar, Harrison-Brown, Middleton, Banati, and Liu (2018) showed that endothelial cells contribute to TSPO expression in the normal brain. In order to determine the contribution of endothelial cells to the TSPO signal in our imaging studies, we used flow cytometry to evaluate endothelial expression.…”
Section: Tspo Upregulation Reflects Pro-inflammatory Microglia/macrmentioning
confidence: 99%
“…A recent study by Betlazar, Harrison-Brown, Middleton, Banati, and Liu (2018) showed that endothelial cells contribute to TSPO expression in the normal brain. In order to determine the contribution of endothelial cells to the TSPO signal in our imaging studies, we used flow cytometry to evaluate endothelial expression.…”
Section: Tspo Upregulation Reflects Pro-inflammatory Microglia/macrmentioning
confidence: 99%
“…43 However, there have been no reports about the relationship between TSPO and GPCR in modulating olfactory behaviors. 46 The strong tspo expression signal was also observed in olfactory nerve layers and glomeruli across the olfactory bulb from the normal mouse brain. tspo RNAi knockdown abrogated the inductive effects of TA on olfactory repulsion.…”
Section: Discussionmentioning
confidence: 95%
“…1 The inhibition of TSPO by Ro5-4864 has been shown to prevent the function of GPCRs in mesenteric postcapillary venules in vivo, and TSPO acts as a modulator of pathways of neutrophil adhesion and locomotion induced by GPCR signaling, thus connecting TSPO functions with the onset of an innate inflammatory response. [44][45][46][47] Earlier studies of tspo expression in the rodent brain using autoradiography with the prototypical tspo ligand PK 11195, indirectly revealed that TSPO-binding sites in the olfactory bulb, particularly in the lateral olfactory tract. 43 However, there have been no reports about the relationship between TSPO and GPCR in modulating olfactory behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations